Daylight in Existing Buildings - A Comparative Study of Calculated Indicators for Daylight - Sara, Eriksson; Waldenström, Lovisa (My University, 2016)
Daylight is an important part when designing a building. It is vital to have a good level of daylight in rooms where people stay for extended periods of time since it has been proven that a lack of daylight affects people’s health and wellbeing in a negative way. Daylight in building is getting more and more important since densified cities and energy efficient buildings are likely to decrease the access of daylight in buildings. People also spends more time indoors in general. This Master’s Thesis is a pilot study to the extensive study “Moderniserad dagsljusstandard” that “Svenska Byggbranschens Utvecklingsfond” (SBUF) is financing. The purpose with the study is to renew the Swedish standard regarding daylight in buildings. This Master’s Thesis aims to identify the daylight factor levels in existing buildings and evaluate different indicators for measuring daylight factor. The studied buildings in this thesis consists of eight residential buildings, two student apartment buildings, two offices, two schools and two hospitals and all of them are located in the region of Gothenburg. The softwares used for modelling and simulations in this work are; AutoCAD, Rhinoceros, Grasshopper and Radiance in DIVA which is a plug-in to Rhino. This Master’s Thesis concludes that there are an extensive amount of rooms in the studied buildings that do not fulfill the demands of a daylight factor above 1%. The indicator used for calculating the daylight factor according to the current Swedish standard has a lot of weaknesses and difficulties and needs to be improved.
Keywords: Byggnadsteknik; Materialvetenskap; Building engineering; Materials Science